Business Plan for “ComforBank” : Online banking system and its application in Azerbaijan - Alizada, Fidan (ADA University, 2022)
In this Business Plan, the new online banking application which is called “ComforBank” will be introduced. The main point of building this application is to facilitate bank orders by customers and accepting orders by banks. Several problems by customers and banks, their interest toward that kind application are identified and analyzed through surveys. In this paper, detailed information about how this application will be used, what will be the advantages will be introduced. In addition, we will show how many workers and which departments we are going to have are shown clearly. Obviously, we will need to have marketing plan in order to demonstrate this new application to people and banks in terms of attracting people’s and banks’ attention and observing improvement on this application. Furthermore, from the financial side, we will introduce the costs and revenue, and funding request for building this online banking application. We will use Profit & Loss statement, Cash Flow Statement for 5 years and at the end, through Breakeven analysis, we are going to show the change over the years.
Keywords: Online banking.; Banking sector.; Business plan.; Business